Local Ecological Knowledge Reveals Change in Seagrass Social–Ecological Systems - Benjamin L. H. Jones; Richard K. F. Unsworth; Lina M. Nordlund; Rohani Ambo-Rappe; Yayu A. La Nafie; Mary Rose Lopez; Susantha Udagedara; Leanne C. Cullen-Unsworth (Oceans, 2022)
It is widely recognized that humanity is currently facing multiple planetary crises, including the widespread loss of biodiversity and a rapidly changing climate. The impacts of these crises are often far reaching and threaten food security (SDG goal two: zero hunger). Small-scale fisheries are estimated to provide livelihoods for over one hundred million people and sustenance for approximately one billion people but face a plethora of threats and challenges linked to planetary crises. In this multi-country assessment (150 coastal villages across five countries within the Indo-Pacific), household interviews revealed how seagrass meadows are important to small-scale fisheries, particularly as a place to find and collect a reliable source of food. Interviews also revealed that habitat loss and the over-exploitation of these resources are placing people and their food security at risk. This study exposed how dynamic local ecological knowledge can be, uncovering personal opinions and responsibilities that result in the hybridization of knowledge. Here, we demonstrate the importance of using local ecological knowledge to incorporate shared values into management but also highlight that an integrated approach, pairing local and conventional scientific knowledge, is needed urgently if we are to meet the needs of people while simultaneously conserving biodiversity.